Preparation method of Al-5. 8Zn-2.2 Mg-0. 2Er-0.12 Zr aluminum alloy plate

By adding rare earth elements such as Er and Zr to the Al-Zn-Mg alloy and adopting a multi-step processing technology to form a complex and synergistic alloy microstructure, the shortcomings of traditional alloys in corrosion performance are solved and its corrosion resistance in harsh environments is significantly improved.

CN119530620AActive Publication Date: 2025-02-28NORTHEAST LIGHT ALLOY CO LTD

Patent Information

Application Number
CN202411600693.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-28
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

Traditional Al-Zn-Mg alloys have shortcomings in corrosion performance, especially in harsh environments, which lead to structural failure and safety accidents.

Method used

By adding rare earth elements such as Er and Zr to the Al-Zn-Mg alloy, the composition and processing technology of the alloy are optimized, including remelting, refining, ceramic filtration, homogenizing annealing, rolling, solid solution quenching and tensile treatment, forming an alloy microstructure with complex synergistic effects.

Benefits of technology

The corrosion performance of Al-Zn-Mg alloy is significantly improved, so that it reaches a high level in room temperature tensile strength and yield strength, and at the same time, the peeling corrosion reaches N or P grade, exceeding the corrosion performance of Al-Zn-Mg alloys of the same level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530620A_ABST
    Figure CN119530620A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an Al-5. 8Zn-2.2 Mg-0. 2Er-0.12 Zr aluminum alloy plate, belongs to the field of preparation of aluminum alloy plates, and particularly relates to a preparation method of an Al-5. 8Zn-2.2 Mg-0. 2Er-0.12 Zr aluminum alloy plate. The invention aims to enable the Al-Zn-Mg alloy to have high strength and greatly improve the corrosion resistance of the alloy at the same time. The preparation method comprises the following steps: weighing, smelting, refining, filtering, casting, homogenizing annealing and milling surface treatment, hot rolling, solid solution treatment, stretching, aging and sawing to obtain a finished product according to the contained elements. According to the components of the alloy, two normal-temperature tensile strength and exfoliation corrosion results are obtained through coordination and matching of homogenizing annealing, solid solution stretching and aging technological systems. And users can select according to the use environment, and the requirements of major engineering fields such as ships, ocean engineering and rail transit can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aluminum alloy plate preparation, and specifically relates to a preparation method of an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate. Background Art

[0002] In many application scenarios of modern industry, the requirements for material strength are getting higher and higher. For example, in the field of aerospace, the structural components of aircraft need to withstand huge flight loads, complex stress states and harsh environmental conditions. Al-Zn-Mg alloy has become one of the candidate materials for manufacturing key components such as aircraft beams and wings due to its high-strength characteristics that can be obtained through processes such as heat treatment. In the field of transportation, the demand for lightweighting of automobiles, high-speed trains, etc. has prompted the use of high-strength alloys to reduce weight while ensuring the safety and reliability of the structure. Therefore, Al-Zn-Mg alloy has also attracted much attention.

[0003] However, although the traditional Al-Zn-Mg alloy has excellent strength, it has obvious shortcomings in corrosion resistance. Its corrosion problems mainly come from the following aspects:

[0004] Alloy composition and microstructure: Zinc, magnesium and other elements in the alloy will form phases with high electrochemical activity under certain conditions. These phases are more susceptible to corrosion reactions relative to the aluminum matrix. In addition, the microstructural inhomogeneity formed during the solidification and processing of the alloy, such as segregation at the grain boundaries, will also provide a preferential channel for the occurrence of corrosion. The contradiction between corrosion sensitivity and strength is the main reason limiting the development and application of Al-Zn-Mg alloys. The distribution state of the grain boundary precipitation phase and the width of the precipitation-free precipitation zone are the key factors affecting the corrosion resistance of the alloy. In order to obtain intermittently distributed grain boundary precipitation phases, aging processes such as T74, RRA and DRRA have been developed. However, the complex heat treatment process not only increases the difficulty of industrial production, but also the intracrystalline precipitation phase is prone to coarsening, resulting in reduced strength.

[0005] Impact of service environment: In practical applications, Al-Zn-Mg alloys are often exposed to harsh environments such as humidity, salt (such as marine environments), corrosive gases (such as industrial pollution areas), etc. For example, in marine environments, chloride ions in seawater can penetrate the oxide film on the surface of the alloy, causing pitting corrosion, intergranular corrosion and other forms of corrosion, which seriously weaken the structural integrity and service life of the alloy.

[0006] For structural parts that bear important loads, such as key components in the aerospace and transportation fields, the degradation of material properties caused by corrosion may cause structural failure, resulting in serious safety accidents. The cost of replacing and repairing parts caused by corrosion is high. In industrial facilities, frequent replacement of Al-Zn-Mg alloy parts damaged by corrosion not only increases direct material and labor costs, but also causes indirect economic losses due to equipment downtime.

[0007] Therefore, it is extremely necessary to significantly improve the corrosion resistance of Al-Zn-Mg alloy while maintaining its high strength advantage. This will not only expand the application scope of the alloy in more harsh environments, such as marine engineering, coastal infrastructure construction, etc., but also effectively reduce the safety risks and economic losses caused by corrosion, thereby improving the reliability and comprehensive benefits of the product.

[0008] In summary, under the background of high strength demand and prominent corrosion problems, it has become an important technical issue to be solved urgently to make Al-Zn-Mg alloy have high strength while significantly improving its corrosion performance. Summary of the invention

[0009] The purpose of the present invention is to make Al-Zn-Mg alloy have high strength and greatly improve the corrosion performance of the alloy, and to provide a preparation method of Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate.

[0010] A method for preparing an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate is completed by the following steps:

[0011] 1. According to the proportion of mass percentage of Si≤0.15%, Fe≤0.15%, Cu≤0.10%, Mn: 0.2%~0.7%, Mg: 1.5%~2.5%, Zr: 0.05%~0.15%, Er: 0.05%~0.30%, Zn: 5.3%~6.3%, Ti: 0.01%~0.05%, single impurity≤0.05%, total impurity≤0.15% and the balance of Al, weigh aluminum ingots, zinc ingots, magnesium ingots, aluminum-manganese master alloy, aluminum-erbium master alloy, aluminum-zirconium master alloy, aluminum-beryllium master alloy, aluminum-titanium wire, and aluminum-titanium-boron grain refiner for remelting as raw materials;

[0012] 2. Add the weighed aluminum ingots, zinc ingots, aluminum-manganese master alloys, aluminum-zirconium master alloys and aluminum-titanium master alloys to a smelting furnace at a smelting temperature of 750-800°C. When the melt temperature is ≥780°C, add the aluminum-erbium master alloy and keep it warm for 20 minutes, then stir for the first time, and stir for the second time after the melt temperature rises to 780°C and keeps it warm for 20 minutes. When the melt temperature after the second stirring drops to 750°C, add the magnesium ingot and the aluminum-beryllium master alloy, stir and mix well, spread the 2# covering agent, let it stand for 20-30 minutes, then introduce the melt into a standing furnace, and use Ar-Cl2 mixed gas to refine it until the hydrogen content in every 100 grams of the melt is ≤0.15mL to obtain an aluminum alloy melt;

[0013] 3. The aluminum alloy melt is filtered through a 30ppi+50ppi double-stage ceramic filter. When casting begins, an aluminum-titanium-boron grain refiner is inserted into the flow channel and the adding speed is controlled. The obtained aluminum alloy melt is poured into a square crystallizer with a specification of 420×1620mm to obtain an alloy ingot.

[0014] 4. The alloy ingot is subjected to homogenization annealing treatment to obtain an ingot after homogenization annealing, and then subjected to milling treatment; the ingot subjected to milling treatment is rolled, and after rolling, solid solution quenching and stretching treatment are performed to obtain a plate after solid solution quenching and stretching;

[0015] 5. The plate after solution quenching and stretching is subjected to aging treatment, and then the finished product is sawn to obtain Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate.

[0016] Beneficial effects of the present invention:

[0017] The Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate prepared by the present invention can meet the needs of major engineering fields such as ships and rail transit.

[0018] The present invention is based on the existing Al-Zn-Mg aluminum alloy component system, and rare earth elements such as Er and Zr are added to further play the complex mutual synergistic effect of the composite addition of rare earth microalloying elements. Explore a new model of Er-Zr multi-component composite alloy design. Adding Er element is one of the ways to improve the corrosion performance of Al-Zn-Mg alloy. The introduction of Al3 (Er, Zr) particles reduces the degree of recrystallization of the alloy and reduces the number of recrystallized grain boundaries in the alloy. The grain boundary precipitation phase tends to precipitate preferentially on the large-angle grain boundaries of recrystallized grains with higher energy. Coarse grain boundary precipitation phases are prone to anodic dissolution, while large-angle grain boundaries with more grain boundary precipitation phases provide expansion channels for crack propagation. The presence of a precipitation-free precipitation zone near the large-angle grain boundary is also believed to reduce the corrosion resistance of the alloy. Since the large-angle grain boundary has a higher interface energy, it is conducive to the nucleation of the precipitation phase, so the precipitation-free precipitation zone at the large-angle grain boundary is wider. Due to the potential difference between the non-precipitation zone and the grain boundary precipitation phase, local corrosion is likely to occur between the two, eventually leading to intergranular corrosion cracks in the alloy, which deteriorates the corrosion resistance of the alloy. Figure 1 As shown in the figure, compared with the alloy without Er, the alloy with Er added has a lower degree of recrystallization, fewer large-angle grain boundaries, and significantly reduced crack propagation paths, so the corrosion resistance of the alloy containing Er is improved. The alloy has the best mechanical properties, and the corrosion resistance can also be improved.

[0019] With the increase of alloying degree, the strength of Al-Zn-Mg alloy gradually increases, but the corrosion resistance deteriorates significantly, which is the main problem restricting the development of Al-Zn-Mg alloy. In the present invention, under the premise that the main alloying element Zn+Mg is 7wt%, the Zn / Mg ratio is optimized, and micro-alloying elements Er and Zr are added, and the influence of Zn / Mg ratio and micro-alloying elements on the mechanical properties and corrosion properties of the alloy are studied, so as to maximize the development of the alloy strength potential, avoid the deterioration of corrosion resistance caused by the increase of alloy content, and further promote the application of Al-Zn-Mg alloy in the fields of ships, rail transportation, etc.

[0020] The present invention improves the corrosion performance of Al-Zn-Mg alloy plates. The prepared Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plates have an exfoliation corrosion performance of N level when the room temperature tensile strength is ≥430MPa, the yield strength is ≥350MPa, and the elongation is ≥12%; and an exfoliation corrosion performance of P level when the room temperature tensile strength is ≥540MPa, the yield strength is ≥520MPa, and the elongation is ≥10%, which is 2 to 3 levels higher than that of Al-Zn-Mg alloys of the same level. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a physical photo of the alloy ingot in Example 2;

[0022] Figure 2 This is a photo of the hot-rolled alloy plate in Example 2;

[0023] Figure 3 This is a photo of the plate after exfoliation and corrosion in Example 2. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0025] Specific implementation method 1: In this implementation method, a method for preparing an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate is completed by the following steps:

[0026] 1. According to the proportion of mass percentage of Si≤0.15%, Fe≤0.15%, Cu≤0.10%, Mn: 0.2%~0.7%, Mg: 1.5%~2.5%, Zr: 0.05%~0.15%, Er: 0.05%~0.30%, Zn: 5.3%~6.3%, Ti: 0.01%~0.05%, single impurity≤0.05%, total impurity≤0.15% and the balance of Al, weigh aluminum ingots, zinc ingots, magnesium ingots, aluminum-manganese master alloy, aluminum-erbium master alloy, aluminum-zirconium master alloy, aluminum-beryllium master alloy, aluminum-titanium wire, and aluminum-titanium-boron grain refiner for remelting as raw materials;

[0027] 2. Add the weighed aluminum ingots, zinc ingots, aluminum-manganese master alloys, aluminum-zirconium master alloys and aluminum-titanium master alloys to a smelting furnace at a smelting temperature of 750-800°C. When the melt temperature is ≥780°C, add the aluminum-erbium master alloy and keep it warm for 20 minutes, then stir for the first time, and stir for the second time after the melt temperature rises to 780°C and keeps it warm for 20 minutes. When the melt temperature after the second stirring drops to 750°C, add the magnesium ingot and the aluminum-beryllium master alloy, stir and mix well, spread the 2# covering agent, let it stand for 20-30 minutes, then introduce the melt into a standing furnace, and use Ar-Cl2 mixed gas to refine it until the hydrogen content in every 100 grams of the melt is ≤0.15mL to obtain an aluminum alloy melt;

[0028] 3. The aluminum alloy melt is filtered through a 30ppi+50ppi double-stage ceramic filter. When casting begins, an aluminum-titanium-boron grain refiner is inserted into the flow channel and the adding speed is controlled. The obtained aluminum alloy melt is poured into a square crystallizer with a specification of 420×1620mm to obtain an alloy ingot.

[0029] 4. The alloy ingot is subjected to homogenization annealing treatment to obtain an ingot after homogenization annealing, and then subjected to milling treatment; the ingot subjected to milling treatment is rolled, and after rolling, solid solution quenching and stretching treatment are performed to obtain a plate after solid solution quenching and stretching;

[0030] 5. The plate after solution quenching and stretching is subjected to aging treatment, and then the finished product is sawn to obtain Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate.

[0031] In this embodiment, the addition amount of the aluminum-beryllium master alloy is 0.005%, which is a very small amount and is used to prevent the ingot from cracking.

[0032] In this embodiment, the aluminum-erbium master alloy is stirred twice to make it evenly distributed in the aluminum alloy melt.

[0033] In this embodiment, the aluminum-titanium-boron grain refiner is inserted into the launder while casting until the casting is completed, in order to make it melt evenly into the aluminum alloy melt.

[0034] In the present embodiment, the aging treatment adopts a single-stage and double-stage aging system, matching the two strength levels of 550MPa and 430MPa corrosion performance to N and P levels, in order to allow users to choose according to the usage scenario.

[0035] In this embodiment, the edge trimming process is performed until no cracks are observed by naked eyes at the edge of the wide hot-rolled plate.

[0036] In this embodiment, Zn and Mg are the main components, and the change in their content affects the microstructure, strength and corrosion resistance of the Al-Zn-Mg alloy, especially the content of Mg element has a significant effect on the corrosion performance of the alloy. In the development process of industrial Al-Zn-Mg alloy, the Zn content gradually increases, but the Mg content is controlled between 1 and 3%, the purpose of which is to prevent the corrosion performance from deteriorating due to excess Mg element. Part of the Mg element in the alloy participates in the formation of the precipitation phase and plays a role in precipitation strengthening, and part of the Mg element is dissolved in the matrix, which is defined as excess Mg. The relationship between the corrosion crack growth rate and the excess Mg content is obtained by combining the corrosion test of Al-Zn-Mg alloys with different components. When the excess Mg content is 0.5-2%, the corrosion crack growth rate is the slowest and the corrosion resistance of the alloy is the best. However, when the excess Mg content exceeds 2%, the crack growth rate increases rapidly and the corrosion resistance of the alloy deteriorates significantly. Therefore, optimizing the content of alloy elements can not only ensure the mechanical properties of the alloy, but also improve the corrosion resistance of the alloy.

[0037] The change of Zn / Mg ratio is also an important factor affecting the corrosion resistance of the alloy. When the Zn / Mg ratio increases from 1 to 2, the crack growth rate of Al-Zn-Mg alloy decreases by two orders of magnitude, and the corrosion resistance of the alloy improves rapidly. When the Zn / Mg ratio is kept between 2.7 and 3, the corrosion resistance of the alloy is optimal. With the further increase of Zn / Mg ratio, the crack growth rate gradually increases, and the corrosion resistance of the alloy begins to deteriorate. Therefore, optimizing the Zn / Mg ratio of the alloy can play a direct role in improving the corrosion resistance of the alloy. For alloys with different alloying degrees, the optimal Zn / Mg ratio range also varies. However, there is a lack of research on the correlation between the Zn / Mg ratio and the microstructure and corrosion properties of the alloy.

[0038] The addition of microalloying elements can reduce the grain size and recrystallization degree of the alloy, and improve the distribution state of the precipitation phase at the grain boundary, which in turn helps the strength and corrosion resistance of the alloy to a certain extent, and meets the comprehensive performance required by the alloy in industrial applications.

[0039] The addition of erbium element in the aluminum alloy of this embodiment will form some small and stable second-phase particles. On the one hand, these particles can serve as obstacles to dislocation movement, thereby helping to improve the strength of the alloy; on the other hand, they play a certain protective role on the alloy surface or grain boundaries, hindering the invasion of corrosive media, thereby improving corrosion resistance; compounds formed with other elements are segregated at grain boundaries, filling grain boundary defects and reducing the possibility of grain boundaries as priority corrosion channels; at the same time, zirconium usually forms Al3Zr phase in aluminum alloys, which has high thermal stability and dispersed distribution characteristics; during alloy solidification and subsequent processing, Al3Zr phase can effectively inhibit grain growth and refine grains, which not only improves the strength of the alloy (fine grain strengthening mechanism), but also refines the grains to relatively increase the grain boundary area, and the diffusion path of the corrosive medium at the grain boundary becomes more tortuous, thereby improving the corrosion resistance of the alloy.

[0040] In the smelting process of this embodiment, the smelting temperature is strictly controlled at 750-800°C, and various master alloys are added in a specific order. First, some master alloys are added and kept warm and stirred at a suitable temperature, so that the elements can be more evenly distributed in the melt, reducing the problem of uneven composition caused by local element enrichment; the alloy with uniform composition will have more stable performance during subsequent processing and use, reducing the hidden danger of local corrosion caused by component segregation, and helping to improve corrosion performance. At the same time, uniform component distribution is also important for forming a uniform strengthening phase, which is conducive to ensuring the high strength of the alloy. When the melt temperature is ≥780°C, add the aluminum erbium master alloy and keep it warm for 20 minutes, and then stir it, so as to ensure that the erbium element is better integrated into the melt and plays its role in refining grains and improving performance.

[0041] Ar-Cl2 mixed gas is used for refining until the hydrogen content in every 100 grams of melt is ≤0.15mL. If the hydrogen content in aluminum alloy is too high, it will form defects such as pores during the solidification process. These defects will destroy the continuity and integrity of the alloy and become the starting point of corrosion. Reducing the hydrogen content through refining can effectively reduce the generation of such defects, thereby improving the corrosion resistance of the alloy, and it is also beneficial to ensure the strength of the alloy, because alloys with fewer defects are less likely to experience stress concentration and premature failure when bearing loads.

[0042] The filtration operation can remove inclusions in the melt, such as oxides, impurity particles, etc. If these inclusions exist in the alloy, on the one hand, they may become stress concentration points and reduce the strength of the alloy; on the other hand, they may also destroy the integrity of the oxide film on the surface of the alloy or serve as a channel for the invasion of corrosive media, aggravating corrosion. Removing inclusions by filtering can improve the purity of the alloy, which helps to improve both strength and corrosion resistance. At the beginning of casting, the aluminum titanium boron grain refiner is inserted into the flow channel and the addition speed is controlled. The aluminum titanium boron grain refiner can further refine the grains. Like the role of zirconium in refining grains mentioned above, fine grain strengthening can improve the strength of the alloy. At the same time, refined grains can improve the corrosion resistance of the alloy, because the fine grains make it more difficult for the corrosive medium to diffuse at the grain boundaries, delaying the occurrence of corrosion.

[0043] Homogenizing annealing of alloy ingots can eliminate the component segregation and structural inhomogeneity formed during the solidification process of the ingot. Through homogenizing annealing, the composition and structure of the alloy are made more uniform, which is beneficial to improving the corrosion resistance of the alloy and ensuring its high strength uniformity.

[0044] Rolling can further refine the grains, improve the alloy's organizational morphology, and increase its strength. At the same time, a suitable rolling process can form a certain work-hardening layer on the alloy surface, which can improve the alloy's resistance to corrosive media to a certain extent.

[0045] Solution quenching and stretching treatment can make the strengthening phase in the alloy dissolve and precipitate better, forming a uniformly distributed strengthening phase and improving the strength of the alloy. In this process, the organizational structure of the alloy is optimized, which will reduce some microstructural defects that are prone to corrosion, thereby improving corrosion resistance.

[0046] Aging treatment can further regulate the precipitation state of the strengthening phase in the alloy, so that the alloy can maintain high strength while improving the corrosion resistance of the alloy by optimizing the distribution and morphology of the strengthening phase.

[0047] In summary, the preparation scheme works synergistically from multiple aspects such as alloy composition design, smelting and refining process, filtration and grain refinement, and subsequent processing, so that the Al-Zn-Mg alloy can have high strength while greatly improving the corrosion resistance of the alloy.

[0048] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that: the aluminum-erbium master alloy in step 1 is Al-5% Er master alloy; the aluminum-zirconium master alloy is Al-5% Zr master alloy; the aluminum-manganese master alloy is Al-10% Mn master alloy; the aluminum-titanium master alloy is Al-4% Ti master alloy; the aluminum-beryllium master alloy is Al-11% Be master alloy; the aluminum-titanium-boron grain refiner is Al-5% Ti-1% B alloy. Others are the same as specific embodiment 1.

[0049] Specific implementation method 3: This implementation method is different from specific implementation method 1 in that the first stirring time in step 2 is 5 to 10 minutes, and the second stirring time is 5 to 10 minutes. The rest is the same as specific implementation method 1.

[0050] Specific implementation method 4: This implementation method is different from the specific implementation method 1 in that the amount of the 2# covering agent in step 2 accounts for 0.50-0.55% of the total mass of the melt in the smelting furnace. The rest is the same as the specific implementation method 1.

[0051] Specific embodiment 5: This embodiment differs from specific embodiment 1 in that the volume ratio of argon gas to chlorine gas in the Ar-Cl2 mixed gas in step 2 is (31.5-33): 1. The rest is the same as specific embodiment 1.

[0052] Specific embodiment 6: This embodiment is different from the specific embodiment 1 in that the speed of inserting the aluminum titanium boron grain refiner into the flow channel in step 3 is 450-500 mm / min. Other aspects are the same as the specific embodiment 1.

[0053] Specific embodiment 7: This embodiment differs from specific embodiment 1 in that the cross-sectional specifications of the alloy ingot in step 3 are 420×1620 mm and the length is 4500 mm. The rest is the same as specific embodiment 1.

[0054] Specific implementation eight: This implementation is different from specific implementation one in that: the process parameters of the homogenization annealing treatment in step four are: heating at a temperature of 280°C for 16 to 20 hours, then heating to 470°C, keeping warm for 20 to 28 hours, and air cooling to room temperature after being taken out of the furnace; the process parameters of the milling treatment are: the ingot is milled to 380mm to 400mm; the rolling is to roll the milled ingot into a wide hot-rolled plate with a thickness of 8 to 20mm and a width of ≥1500mm, the maximum reduction of a single pass during the rolling process is 20mm, and the rolling speed is controlled to be 1.2 to 1.5m / s; the process parameters of the solution treatment are: firstly raise the furnace temperature to 470°C, then load the hot-rolled plate into the furnace, monitor the metal temperature of the hot-rolled plate to reach 470°C, start timing and keep warm for 60 minutes, then take out of the furnace and quench with water to obtain the solution-treated plate; the process parameters of the stretching treatment are: the solution-treated plate completes the stretching treatment of the plate within 2 hours, and the stretching amount is controlled at 1.8 to 2.5%. The rest is the same as the first specific implementation mode.

[0055] Specific embodiment 9: This embodiment is different from specific embodiment 1 in that: the process parameters of the aging treatment described in step 5 are: after the plate is kept at a temperature of 120°C for 6 hours, the furnace temperature is raised to 160°C, kept at a temperature of 160°C for 20 hours, and then taken out of the furnace for air cooling, and the plate is sawed to obtain Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plates with tensile strength ≥430MPa, yield strength ≥350MPa, elongation ≥12%, and exfoliation corrosion reaching N level. The rest is the same as specific embodiment 1.

[0056] Specific embodiment ten: This embodiment differs from specific embodiment one in that the process parameters of the aging treatment in step five are: the plate is kept at a temperature of 120°C for 24 hours, air-cooled after being taken out of the furnace, and the plate is sawn to obtain an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate with a tensile strength of ≥540MPa, a yield strength of ≥520MPa, an elongation of ≥10%, and exfoliation corrosion reaching P grade. The rest is the same as specific embodiment one.

[0057] The following examples are used to verify the beneficial effects of the present invention:

[0058] Embodiment 1: A method for preparing an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate is completed by the following steps:

[0059] 1. According to the mass percentage of Si≤0.15%, Fe≤0.15%, Cu≤0.10%, Mn: 0.2%~0.7%, Mg: 1.5%~2.5%, Zr: 0.05%~0.15%, Er: 0.05%~0.30%, Zn: 5.3%~6.3%, Ti: 0.01%~0.05%, single impurity≤0.05%, total impurity≤0.15% and the balance is Al, weigh the aluminum ingot, zinc ingot, magnesium ingot, aluminum ingot for remelting Manganese master alloy, aluminum-erbium master alloy, aluminum-zirconium master alloy, aluminum-beryllium master alloy, aluminum-titanium wire, and aluminum-titanium-boron grain refiner are used as raw materials; the aluminum-erbium master alloy is Al-5% Er master alloy; the aluminum-zirconium master alloy is Al-5% Zr master alloy; the aluminum-manganese master alloy is Al-10% Mn master alloy; the aluminum-titanium master alloy is Al-4% Ti master alloy; the aluminum-beryllium master alloy is Al-11% Be master alloy; and the aluminum-titanium-boron grain refiner is Al-5% Ti-1% B alloy;

[0060] 2. Add the weighed aluminum ingots, zinc ingots, aluminum-manganese master alloys, aluminum-zirconium master alloys and aluminum-titanium master alloys to the melting furnace at a melting temperature of 750-800°C. When the melt temperature is ≥780°C, add the aluminum-erbium master alloy and keep it warm for 20 minutes, then stir it for the first time for 5-10 minutes. When the melt temperature rises to 780°C again and keeps it warm for 20 minutes, stir it for the second time for 5-10 minutes. When the melt temperature after the second stirring drops to 750°C, add A magnesium ingot and an aluminum-beryllium master alloy are stirred and mixed, and then a 2# covering agent is spread, and the mixture is allowed to stand for 20 to 30 minutes. The melt is then introduced into a standing furnace, and an Ar-Cl2 mixed gas is used for refining until the hydrogen content in every 100 grams of the melt is ≤0.15 mL, thereby obtaining an aluminum alloy melt; the amount of the 2# covering agent accounts for 0.50 to 0.55% of the total mass of the melt in the smelting furnace; the volume ratio of argon to chlorine in the Ar-Cl2 mixed gas is (31.5 to 33):1;

[0061] 3. The aluminum alloy melt is filtered through a 30ppi+50ppi double-stage ceramic filter. When casting begins, an aluminum-titanium-boron grain refiner is inserted into the flow channel and the adding speed is controlled. The obtained aluminum alloy melt is poured into a square crystallizer with a specification of 420×1620mm to obtain an alloy ingot. The speed at which the aluminum-titanium-boron grain refiner is inserted into the flow channel is 450-500mm / min. The cross-sectional specification of the alloy ingot is 420×1620mm and the length is 4500mm.

[0062] 4. The alloy ingot is subjected to homogenization annealing treatment to obtain an ingot after homogenization annealing, and then subjected to milling treatment; the ingot subjected to milling treatment is rolled, and after rolling, solid solution quenching and stretching treatment are performed to obtain a plate after solid solution quenching and stretching; the process parameters of the homogenization annealing treatment are: heating at a temperature of 280°C for 16 to 20 hours, then heating to 470°C, keeping warm for 20 to 28 hours, and air cooling to room temperature after being taken out of the furnace; the process parameters of the milling treatment are: the ingot is milled to 380 mm to 400 mm; the rolling is to roll the ingot subjected to the milling treatment into a thickness of 8 to The wide hot-rolled plate with a width of 20mm and a width of ≥1500mm, the maximum reduction of a single pass during the rolling process is 20mm, and the rolling speed is controlled at 1.2-1.5m / s; the process parameters of the solution treatment are: firstly, the furnace temperature is raised to 470℃, and then the hot-rolled plate is loaded into the furnace, and when the metal temperature of the hot-rolled plate reaches 470℃, the timing is started and the heat preservation is carried out for 60min, and then the plate is taken out of the furnace and water quenched to obtain the solution-treated plate; the process parameters of the stretching treatment are: the solution-treated plate is stretched within 2h, and the stretching amount is controlled at 1.8-2.5%;

[0063] 5. The plate after solution quenching and stretching is subjected to aging treatment, and then the finished product is sawn to obtain Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate; the process parameters of the aging treatment are as follows: after the plate is kept at a temperature of 120°C for 6 hours, the furnace temperature is raised to 160°C, and after being kept at a temperature of 160°C for 20 hours, it is taken out of the furnace and air-cooled, and the plate is sawn to obtain Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate with a tensile strength of ≥430MPa, a yield strength of ≥350MPa, an elongation of ≥12%, and exfoliation corrosion reaching N level.

[0064] The Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate prepared in this embodiment was tested and found that when the tensile strength at room temperature was ≥430MPa, the yield strength was ≥350MPa, and the elongation was ≥12%, the exfoliation corrosion reached level N.

[0065] Example 2: The difference between this example and Example 1 is that the process parameters of the aging treatment described in step 5 are as follows: the plate is kept at a temperature of 120°C for 24 hours, then taken out of the furnace and air-cooled, and the plate is sawed to obtain Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate with a tensile strength of ≥540MPa, a yield strength of ≥520MPa, an elongation of ≥10%, and exfoliation corrosion reaching P grade.

[0066] The Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate prepared in this embodiment was tested and found that when the tensile strength at room temperature was ≥540MPa, the yield strength was ≥520MPa, and the elongation was ≥10%, the exfoliation corrosion reached P level.

[0067] The actual photo of the alloy ingot obtained in this embodiment is as follows Figure 1 shown.

[0068] The actual photo of the alloy plate obtained in this embodiment is as follows Figure 2 shown.

[0069] The photo of the alloy plate obtained in this example after exfoliation corrosion is as follows: Figure 3 As shown in the figure, there is no delamination or pitting on the plate, and the surface is smooth.

Claims

1. A method for preparing an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy sheet, characterized in that The preparation method of Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate is completed according to the following steps:

1. According to the proportion of mass percentage of Si≤0.15%, Fe≤0.15%, Cu≤0.10%, Mn: 0.2%~0.7%, Mg: 1.5%~2.5%, Zr: 0.05%~0.15%, Er: 0.05%~0.30%, Zn: 5.3%~6.3%, Ti: 0.01%~0.05%, single impurity≤0.05%, total impurity≤0.15% and the balance of Al, weigh aluminum ingots, zinc ingots, magnesium ingots, aluminum-manganese master alloy, aluminum-erbium master alloy, aluminum-zirconium master alloy, aluminum-beryllium master alloy, aluminum-titanium wire, and aluminum-titanium-boron grain refiner for remelting as raw materials; 2. Add the weighed aluminum ingots, zinc ingots, aluminum-manganese master alloys, aluminum-zirconium master alloys and aluminum-titanium master alloys to a smelting furnace at a smelting temperature of 750-800°C. When the melt temperature is ≥780°C, add the aluminum-erbium master alloy and keep it warm for 20 minutes, then stir for the first time, and stir for the second time after the melt temperature rises to 780°C and keeps it warm for 20 minutes. When the melt temperature after the second stirring drops to 750°C, add the magnesium ingot and the aluminum-beryllium master alloy, stir and mix well, spread the 2# covering agent, let it stand for 20-30 minutes, then introduce the melt into a standing furnace, and use Ar-Cl2 mixed gas to refine it until the hydrogen content in every 100 grams of the melt is ≤0.15mL to obtain an aluminum alloy melt; 3. The aluminum alloy melt is filtered through a 30ppi+50ppi double-stage ceramic filter. When casting begins, an aluminum-titanium-boron grain refiner is inserted into the flow channel and the adding speed is controlled. The obtained aluminum alloy melt is poured into a square crystallizer with a specification of 420×1620mm to obtain an alloy ingot.

4. The alloy ingot is subjected to homogenization annealing treatment to obtain an ingot after homogenization annealing, and then subjected to milling treatment; the ingot subjected to milling treatment is rolled, and after rolling, solid solution quenching and stretching treatment are performed to obtain a plate after solid solution quenching and stretching; 5. The plate after solution quenching and stretching is subjected to aging treatment, and then the finished product is sawn to obtain Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plate.

2. The method for preparing an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy sheet according to claim 1, characterized in that The aluminum-erbium master alloy described in step one is Al-5% Er master alloy; the aluminum-zirconium master alloy is Al-5% Zr master alloy; the aluminum-manganese master alloy is Al-10% Mn master alloy; the aluminum-titanium master alloy is Al-4% Ti master alloy; the aluminum-beryllium master alloy is Al-11% Be master alloy; and the aluminum-titanium-boron grain refiner is Al-5% Ti-1% B alloy.

3. The method for preparing an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy sheet according to claim 1, characterized in that The first stirring time in step 2 is 5 to 10 minutes, and the second stirring time is 5 to 10 minutes.

4. The method for preparing an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy sheet according to claim 1, characterized in that The amount of the 2# covering agent in step 2 accounts for 0.50-0.55% of the total mass of the melt in the smelting furnace.

5. The method for preparing an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy sheet according to claim 1, characterized in that The volume ratio of argon to chlorine in the Ar-Cl2 mixed gas in step 2 is (31.5-33):

1.

6. The method for preparing an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy sheet according to claim 1, characterized in that The speed at which the aluminum-titanium-boron grain refiner is inserted into the flow channel in step three is 450-500 mm / min.

7. The method for preparing the Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy sheet according to claim 1, characterized in that The cross-sectional specifications of the alloy ingot described in step three are 420×1620 mm and 4500 mm in length.

8. The method for preparing the Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy sheet according to claim 1, characterized in that The process parameters of the homogenization annealing treatment in step 4 are as follows: heating at a temperature of 280°C for 16 to 20 hours, then heating to 470°C, keeping warm for 20 to 28 hours, and air cooling to room temperature after being taken out of the furnace; the process parameters of the milling treatment are as follows: the ingot is milled to 380 mm to 400 mm; the rolling is to roll the milled ingot into a wide hot-rolled plate with a thickness of 8 to 20 mm and a width of ≥1500 mm, the maximum reduction of a single pass during the rolling process is 20 mm, and the rolling speed is controlled to be 1.2 to 1.5 m / s; the process parameters of the solution treatment are as follows: first, the furnace temperature is raised to 470°C, and then the hot-rolled plate is loaded into the furnace, and when the metal temperature of the hot-rolled plate reaches 470°C, the timing is started and the plate is kept warm for 60 minutes, and then the plate is taken out of the furnace and quenched in water to obtain a solution-treated plate; the process parameters of the stretching treatment are as follows: the solution-treated plate completes the stretching treatment of the plate within 2 hours, and the stretching amount is controlled at 1.8 to 2.5%.

9. The method for preparing an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy sheet according to claim 1, characterized in that The process parameters of the aging treatment in step five are as follows: after the plate is kept at a temperature of 120° C. for 6 hours, the furnace temperature is raised to 160° C., and after being kept at a temperature of 160° C. for 20 hours, the plate is taken out of the furnace and air-cooled, and the plate is sawed to obtain Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plates with a tensile strength of ≥430MPa, a yield strength of ≥350MPa, an elongation of ≥12%, and exfoliation corrosion reaching N level.

10. The method for preparing an Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy sheet according to claim 1, characterized in that The process parameters of the aging treatment in step five are as follows: the plate is kept at a temperature of 120° C. for 24 hours, taken out of the furnace and air-cooled, and the plate is sawed to obtain Al-5.8Zn-2.2Mg-0.2Er-0.12Zr aluminum alloy plates with a tensile strength ≥540MPa, a yield strength ≥520MPa, an elongation ≥10%, and exfoliation corrosion reaching P grade.

Citation Information

Patent Citations

  • Aluminum alloy sheet for high-speed train structure and manufacture thereof

    CN101914710A

  • Er / Zr-mircoadded Al-Zn-Mg-Cu alloy and preparation technique thereof

    CN104561702A

  • Corrosion-resisting weldable aluminum alloy board for box tank car and manufacturing method of board

    CN107385295A

  • Er-containing high-strength anti-corrosion Al-Zn-Mg aluminum alloy and preparation method

    CN110983130A

  • 700MPa-grade Al-Zn-Mg-Cu series aluminum alloy extruded material and preparation method thereof

    CN115874093A

Cited By

  • Aluminum alloy welding wire material, preparation method thereof and aluminum alloy additive manufacturing product

    CN121083188A